Peculiarities of social competence in children with different autistic levels - Оstrovska Kateryna (Journal of Education Culture and Society, 2020)
The results of research of the social competence forming process in children with autistic disorders are presented in this work. It has been determined that the social competence range in children is dependent on the autism level. The factors of social adaptation in the children with different autism levels have been analyzed.